Fatty Acid Accumulations and Transcriptome Analyses Under Different Treatments in a Model Microalga Euglena gracilis - He, Jiayi; Du, Ming; Chen, Yehua; Liu, Yerong; Zhang, Jinlin (Kenny); Fu, Wen; Lei, Anping; Wang, Jiangxin (Frontiers in Chemical Engineering, 2022)
With the continuous growth of the world’s population and the increasing development of industrialization, the demand for energy by human beings has been expanding, resulting in an increasingly severe energy crisis. Microalgae are considered the most potential alternatives to traditional fossil fuels due to their many advantages, like fast growth rate, strong carbon sequestration capacity, and low growth environment requirements. Euglena can use carbon sources such as glucose, ethanol, and others for heterotrophic growth. Moreover, Euglena is highly adaptable to the environment and has a high tolerance to various environmental stresses, such as salinity, heavy metals, antibiotics, etc. Different treatments of Euglena cells could affect their growth and the accumulation of bioactive substances, especially fatty acids. To expand the industrial application of Euglena as a potential biodiesel candidate, we determine the physiological responses of Euglena against environmental stresses (antibiotics, heavy metals, salinity) or carbon resources (glucose and ethanol), and evaluate the potential for higher quality and yield of fatty acid with a high growth rate. Adding glucose into the culture media increases cell biomass and fatty acid production with high-quality biodiesel characters. The transcriptome analysis helped explore the possible regulation and biosynthesis of fatty acids under different treatments and exploited in the improvement of biodiesel production. This study provides insights for further improvement and various culture treatments for Euglena-based biodiesel and jet fuels.